2022
DOI: 10.1007/s10670-022-00613-y
|View full text |Cite
|
Sign up to set email alerts
|

Backwards Causation in Social Institutions

Abstract: Whereas many philosophers take backwards causation to be impossible, the few who maintain its possibility either take it to be absent from the actual world or else confined to theoretical physics. Here, however, I argue that backwards causation is not only actual, but common, though occurring in the context of our social institutions. After juxtaposing my cases with a few others in the literature and arguing that we should take seriously the reality of causal cases in these contexts, I consider several objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…In his wonderfully thought-provoking article "Backwards Causation in Social Institutions", Silver (2022) argues that if we take so-called "institutional facts" seriously, then we are led to conclude that backwards causation is not only possible, but commonplace. As such, Silver is not the first to argue that backwards causation is logically possible (others who have argued this include Dummett, 1954Dummett, , 1964Lewis, 1976;Roache, 2009;Tooley, 1999), nor is he the first to argue that backwards causation is actual (Dowe, 1997;Price, 1997;and Corry, 2015, for example, have suggested that backwards causation may account for the weirdness found in quantum mechanics), and nor is he the first to argue that backwards causation might occur amongst institutional facts (Barlassina & Del Prete, 2015;and Torrengo, 2018 suggest this also).…”
Section: Introductionmentioning
confidence: 99%
“…In his wonderfully thought-provoking article "Backwards Causation in Social Institutions", Silver (2022) argues that if we take so-called "institutional facts" seriously, then we are led to conclude that backwards causation is not only possible, but commonplace. As such, Silver is not the first to argue that backwards causation is logically possible (others who have argued this include Dummett, 1954Dummett, , 1964Lewis, 1976;Roache, 2009;Tooley, 1999), nor is he the first to argue that backwards causation is actual (Dowe, 1997;Price, 1997;and Corry, 2015, for example, have suggested that backwards causation may account for the weirdness found in quantum mechanics), and nor is he the first to argue that backwards causation might occur amongst institutional facts (Barlassina & Del Prete, 2015;and Torrengo, 2018 suggest this also).…”
Section: Introductionmentioning
confidence: 99%